Long-Term Dose-Response Condensed Tannin Supplementation Does Not Affect Iron Status or Bioavailability - Delimont, Nicole M.; Fiorentino, Nicole M.; Kimmel, Katheryne A.; Haub, Mark D.; Rosenkranz, Sara K.; Lindshield, Brian L. (My University, 2017)
Background: Repeated phytic acid consumption leads to iron absorption adaptation but, to the best of our knowledge, the impact of repeated tannin consumption has not yet been established. Salivary proline-rich proteins (PRPs) may improve iron absorption by precipitating tannins. Objectives: This study aimed to determine the effect of long-term, dose-response condensed tannin supplementation on iron bioavailability and status and to assess the effect of salivary proteins on iron bioavailability during prolonged condensed tannin consumption. A secondary objective was to assess astringency as a potential marker for adaptation to tannins and iron bioavailability. Methods: Eleven nonanemic women were enrolled in a double-blind 3-dose crossover trial. Three (1.5, 0.25, or 0.03 g) condensed tannin supplements were consumed 3 times/d for 4 wk in random order, with 2-wk washouts in between. Meal challenges were employed before and after supplementation to assess iron bioavailability, iron status, salivary PRP changes, and astringency. Results: Tannin supplementation in any dose did not change iron bioavailability at any dose (P . 0.82) from weeks 0 to 4. Hemoglobin (P = 0.126) and serum ferritin (P = 0.83) were unchanged by tannin dose from weeks 0 to 4. There were signiﬁcant correlations among tannin supplementation and iron bioavailability, basic proline-rich proteins (bPRPs) (r = 0.366, P = 0.003), and cystatin production (r = 0.27, P = 0.03). Astringency ratings did not change signiﬁcantly within or between tannin doses (P . 0.126), but there were negative relations among bPRP (r , 20.32, P , 0.21), cystatin production (r , 20.2, P , 0.28), and astringency ratings. Conclusions: Condensed tannin consumption did not affect iron bioavailability or status regardless of the supplementation period in premenopausal nonanemic women. Correlation analyses suggest that bPRPs and cystatins are associated with improved iron bioavailability and that lower ratings of astringency may predict improved iron absorption with repeated tannin consumption. Curr Dev Nutr 2017;1:e001081.
Citation: Delimont, N. M., Fiorentino, N. M., Kimmel, K. A., Haub, M. D., Rosenkranz, S. K., & Lindshield, B. L. (2017). Long-Term Dose-Response Condensed Tannin Supplementation Does Not Affect Iron Status or Bioavailability. Current Developments in Nutrition, 1(10), e001081. https://doi.org/10.3945/cdn.117.001081
Keywords: Tannins; Iron bioavailability; Salivary proline-rich proteins; Adaptation; Antinutritional factors; proanthocyanidins